Pharmaceutical Nanotechnology: A Therapeutic Revolution - Douglas Dourado (International Journal of Pharmaceutical Sciences and Developmental Research - Peertechz Publications, 2020)
The definition of nanotechnology is not yet a consensus in the scientific community. Among the most widespread concepts, it can be defined as the science that studies nanoscale materials (1 to 1000 nm) involving areas such as materials engineering, energy, biotechnology, physics and pharmacy, among others [1]. It is based on the development of nanostructures, providing revolutionary applications in various sciences [2]. Among the applications of nanotechnology is the pharmaceutical nanotechnology, a developed expertise mainly by pharmacists, engineers and biotechnologists. Regarding to pharmaceutical nanotechnology, it is based on the life sciences, which allows the development of nanostructures capable of promoting innovative drug delivery systems as therapeutic alternatives to various pathologies, as well as biosensors of nanomaterials to perform advanced diagnostics.